Through using substitution how can I solve
3p-3 = q
and
7p=1+4q
so that p=-1 and q=-2
I am really interested in the working out, the how and the why. If that makes sense.
Many Thanks in advance
Yes, but you see the first equation is q=..., so you can directly substitute $\displaystyle q=3p-3$ in the second one therefore you get:
$\displaystyle 7p=1+4(3p-3)$
Solve this equation for $\displaystyle p$, afterwards you can find $\displaystyle q$
No problem, it's just the same way. If you divide in the first equation every side by 3 then you get $\displaystyle p-1=q$, now substitute this in the second equation therefore the equation becomes:
$\displaystyle 7p=1+4(p-1)$
What do you get for $\displaystyle p$? And $\displaystyle q$?